Management of Sports Recreation Basil Beach Tourism in Kendal Regency - Sholahudin, Athoilah (Universitas Negeri Semarang, 2023)
Abstract. This study aims to analyze the management of recreational sports in Kemangi Beach Tourism in Kendal Regency. The research method used is a qualitative method with a qualitative descriptive approach. The research location is Indah Kemangi Beach, Jungsemi Village, Cepiring District, Kendal Regency. The research was conducted in June 2023. Instruments and data collection methods include interviews, observation, and documentation. Interview guides are used to guide interactions with tourist attraction managers, while tape recorders are used to record interviews. Direct observations were made at Pantai Indah Kemangi to gain a deeper understanding of recreational sports management. In addition, data was also obtained through documentation from the tourism object manager. The results of this study describe a comprehensive picture of recreational sports management at Pantai Indah Kemangi. Management related to facilities, human resources, environmental awareness, as well as challenges and opportunities identified from the perspective of managers and management of tourism objects. These findings provide an in-depth understanding of tourism management efforts that focus on recreational sports. This research provides a valuable contribution to efforts to improve and develop recreational sports management in similar destinations. Directed at improving services, training human resources, and integrating sustainable principles, the results of this study are expected to be a guide for the desire and improvement of the quality of the tourist experience at Pantai Indah Kemangi.Abstract in Indonesia. Penelitian ini bertujuan untuk menganalisis manajemen olahraga rekreasi di Wisata Pantai Kemangi di Kabupaten Kendal. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif kualitatif. Lokasi penelitian adalah Pantai Indah Kemangi Desa Jungsemi Kecamatan Cepiring Kabupaten Kendal. Penelitian dilaksanakan pada bulan Juni 2023. Instrumen dan metode pengumpulan data melibatkan wawancara, observasi, dan dokumentasi. Pedoman wawancara digunakan untuk memandu interaksi dengan pengelola objek wisata, sementara alat perekam digunakan untuk merekam wawancara. Observasi langsung dilakukan di Pantai Indah Kemangi untuk mendapatkan pemahaman yang lebih mendalam tentang manajemen olahraga rekreasi. Selain itu, data juga diperoleh melalui dokumentasi dari pengelola objek wisata. Hasil penelitian ini menggambarkan gambaran yang komprehensif tentang manajemen olahraga rekreasi di Pantai Indah Kemangi. Pengelolaan terkait fasilitas, sumber daya manusia, kesadaran lingkungan, serta tantangan dan peluang diidentifikasi dari perspektif para pengelola dan pengelolaan obyek wisata. Temuan ini memberikan pemahaman mendalam tentang upaya pengelolaan wisata yang berfokus pada olahraga rekreasi. Penelitian ini memberikan sumbangan berharga bagi upaya perbaikan dan pengembangan manajemen olahraga rekreasi di destinasi serupa. Diarahkan pada peningkatan layanan, pelatihan sumber daya manusia, dan integrasi prinsip-prinsip berkelanjutan, hasil penelitian ini diharapkan dapat menjadi pedoman bagi keberlanjutan dan peningkatan kualitas pengalaman wisatawan di Pantai Indah Kemangi.